Transforming Indigenous Mindsets: The Impact of Floating Nature Schools on Suku Anak Dalam Education - Sinta Nurjulaiha; Junaidi Irwandi; Susi Fitria Dewi; Yurni Suasti (STAI Hubbulwathan Duri, 2025)
Indigenous communities such as the Suku Anak Dalam (SAD) in South Sumatra have historically viewed formal education as irrelevant or even threatening to their cultural identity. This study investigates how non-formal, culturally responsive education—delivered through a